Impact of HIV on Cognitive Performance in Professional Drivers. (15th April 2022) - Gouse, Hetta; Masson, Catherine J.; Henry, Michelle; Dreyer, Anna; Robbins, Reuben N.; Kew, Greg; Joska, John A.; London, Leslie; Marcotte, Thomas D.; Thomas, Kevin G. F.
Abstract : Background: The intellectually demanding modern workplace is often dependent on good cognitive health, yet there is little understanding of how neurocognitive dysfunction related to HIV presents in employed individuals working in high-risk vocations such as driving. HIV-associated neurocognitive impairment is also associated with poorer long-term cognitive, health, and employment outcomes. Setting: This study, set in Cape Town, South Africa, assessed the effects of HIV on neuropsychological test performance in employed male professional drivers. Method: We administered a neuropsychological test battery spanning 7 cognitive domains and obtained behavioral data, anthropometry, and medical biomarkers from 3 groups of professional drivers (68 men with HIV, 55 men with cardiovascular risk factors, and 81 controls). We compared the drivers' cognitive profiles and used multiple regression modeling to investigate whether between-group differences persisted after considering potentially confounding sociodemographic and clinical variables (ie, income, home language, depression, and the Framingham risk score). Results: Relative to other study participants, professional drivers with HIV performed significantly more poorly on tests assessing processing speed ( P < 0.003) and attention and working memory ( P = 0.018). Group membership remained a predictor of cognitive performance after controlling for potential confounders. The cognitive deficits observed in men with HIV were, however, largely characterized as being mild or asymptomatic. Consistent with this characterization, their relatively poor performance on neuropsychological testing did not generalize to self-reported impairment on activities of daily living. Conclusion: Drivers with HIV may be at risk of poorer long-term health and employment outcomes. Programs that monitor and support their long-term cognitive health are needed.